(untitled) (World Science, 2020)
In the 21st century, when medicine seemed to be steadily progressing and developing, studying and applying new methods of diagnosis and treatment of infectious diseases in order to prevent the occurrence of epidemics, a new infectious agent (virus) of the respiratory system appears, which has the ability of emergence, causes a rather high mortality rate among the population and triggers experts’ concern about the unpredictability of the evolution of the virus. This article provides a brief analysis of the literature on coronaviruses and the diseases they can cause in humans, in particular the clinical features in childhood.